DNA methylation-based profiling of uterine neoplasms: a novel tool to improve gynecologic cancer diagnostics - Kommoss, Felix; Stichel, Damian; Schrimpf, Daniel; Kriegsmann, Mark; Tessier-Cloutier, Basile; Talhouk, Aline; McAlpine, Jessica N.; Chang, Kenneth T. E.; Sturm, Dominik; Pfister, Stefan; Romero-Pérez, Laura; Kirchner, Thomas; et al. (Journal of cancer research and clinical oncology, 2020)
Uterine neoplasms comprise a broad spectrum of lesions, some of which may pose a diagnostic challenge even to experienced pathologists. Recently, genome-wide DNA methylation-based classification of central nervous system tumors has been shown to increase diagnostic precision in clinical practice when combined with standard histopathology. In this study, we describe DNA methylation patterns of a diverse set of uterine neoplasms and test the applicability of array-based DNA methylation profiling.